E0158 Transient prehypertensive treatment in spontaneously hypertensive rats: a comparison of losartan and amlodipine regarding long-term blood pressure and cardiac protection. (17th November 2010) - Lin, Jinxiu; Lin, Liming; Tang, Hong; Xu, Changsheng
Abstract : Aims: To compare the effectiveness of transient prehypertensive treatment with losartan versus amlodipine in spontaneously hypertensive rats (SHR) on long-term blood pressure and cardiac protection Main methods SHR were prehypertensively (weeks 4–10 of age) treated with losartan (SHR-Los: 20 mg/kg/day), amlodipine (SHR-Aml: 10 mg/kg/day) or saline (n=24 each group). Rats were followed up until week 46. Systolic blood pressure (SBP) was measured by tail-cuff method. Cardiac parameters including Left ventricular (LV) mass index (LVMI), collagen volume fraction (CVF) and LV function were assessed by histomorphometry and echocardiography. Plasma and myocardium angiotensin II (Ang II) and aldosterone (Aldo) were measured by radioimmunoassay. Cardiac angiotensin II type 1 and type 2 receptor (AT1R and AT2R) protein were determined by immunoblotting and brain natriuretic peptide (BNP) mRNA was semi-quantified by reverse transcription-PCR (RT-PCR). Key findings: The SBP in SHR-Los was reduced until age 46 weeks, but returned to untreated SHR levels in SHR-Aml from 30 weeks onwards. Compared to untreated SHR, the LVMI and CVF in SHR-Los were markedly decreased until week 46, and the LV ejection fraction (LVEF) (SHR-Los vs SHR: 83.1±2.3% vs 79.5±1.9%, p<0.05) and cardiac BNP mRNA expression were improved, whereas comparable LVMI and elevated CVF were found in SHR-Aml, and the LVEF fell significantly below that of untreated SHR at week 46 (SHR-Aml vs SHR: 74.4±4.3% vs 79.5±1.9%, p<0.05), with cardiac BNP mRNA expression increasing slightly. Compared to untreated SHR, the plasma and myocardium Ang II and Aldo levels in SHR-Los at week 46 were remarkably decreased (plasma Ang II: 302±32 vs 458±32 pg/ml; plasma Aldo: 172±20 vs 252±41 pg/ml; cardiac Ang II: 126±11 vs 199±14 pg/100 mg; cardiac Aldo: 497±43 vs 766±46 pg/100 mg, all p<0.05), and the cardiac AT1R protein was down-regulated and AT2R protein was up-regulated, no significant difference of these indices was found between SHR-Aml and untreated SHR. Significance Prehypertensive treatment with losartan was more effective than amlodipine on delaying long-term blood pressure rise and meliorating cardiac structure and function, which might be related to permanent attenuation of circulating and local renin-angiotensin (R-A) systems.